Glass alumina composites for functional and structural applications. Issue 9 (15th June 2019) - Dursun, Gülsüm Meryem; Duran, Cihangir
Abstract: A SiO2 -Al2 O3 -CaO based glass was mixed with Al2 O3 at various ratios to fabricate composites for functional and structural applications such as substrate, low temperature co-fired ceramics and radomes, which necessitates a thorough characterization of mechanical, thermal and dielectric properties. The optimum densification temperatures decreased from 1350 °C (20 wt% glass) to 1200 °C (40 wt% glass), and to 850 °C (50–60 wt% glass) due to liquid phase sintering for the samples with 20 and 40 wt% glass, and viscous sintering for the samples with 50-60 wt% glass. Main phase was Al2 O3 as well as anorthite crystallized after 825 °C. Glass addition decreased the mechanical properties such as Young's modulus from 231 GPa (20 wt% glass) to 105 GPa (60 wt% glass), flexural strength from 387 MPa (20 wt% glass) and 213 MPa (60 wt% glass). Dielectric constant and dielectric loss of the composites with 20-60 wt% glass were 8.76–7.32 and 0.0022–0.0081 at 5 MHz, respectively. Thermal expansion coefficient also decreased with increasing glass content from 7.72 ppm/°C (20 wt% glass) to 6.66 ppm/°C (60 wt% glass). The composites with 50-60 wt% glass were suitable for substrate and low temperature co-fired ceramic applications due to lower densification temperatures (<950 °C), lower dielectric properties together with optimized mechanical and thermal properties. The composite with 55 wt% glass was then successfully fabricated by tape casting and co-fired with silver electrode, without any additional phase formation and shape distortion. In addition, the composites with 20 and 40 wt% glass were promising candidates for structural radome applications to be used at high temperatures due to their low thermal expansion coefficient and Young's modulus together with low dielectric properties.